A combination of TDM and KSAM to determine initial feasible solution of transportation problems - Muhammad Sam'an; Ifriza, Yahya Nur (SHM Publisher, 2021)
In case of the Transportation Problem (TP), it was found that TP had equal the smallest so that the existing methods will be generated two or more IFS values. The newly developed algorithm is generated through a combination of Total Difference Method (TDM) and Karagul-Sahin Approximation Method (KSAM) algorithm, is capable to determine the initial feasible solution of TP. Based on the numerical illustration of TP example to evaluate the performance of the new proposed algorithm. The computational performances have been compared to the existing methods (TDM1 and KSAM) and the results shown this algorithm achieved better performance than the existing methods for TP example.